Sustainable Hazard Mitigation: Exploring the Importance of Green Infrastructure in Building Disaster Resilient Communities - Tyler, Jenna (Consilience, 2016)
Natural disasters continue to plague the United States, undermining the nation’s ability to build disaster resilient communities. Although structural and non-structural mitigation measures are currently in place to lessen the impact natural disasters have on society, little attention has been given to the construction of green infrastructure as a sustainable hazard mitigation strategy. The purpose of this article is to explore the benefits of green infrastructure as a sustainable hazard mitigation strategy and offer recommendations to public sector entities to build disaster resilient communities.